Crossing the Line at Altitude: Passenger Sexual Misconduct in the Skies, 1999-2021 - Vieraitis, Lynne M. (Journal of crime and justice, 2025)
Over the past decade, a range of news outlets and social media platforms has increasingly featured reports of airline passenger misconduct, particularly those involving verbal and physical assault. Less attention has been paid to passenger sexual misconduct. To improve our understanding of the nature and types of air passenger sexual misconduct cases, we draw on data from 77 incidents reported from 1999 to 2021 to develop a multi-classification scheme of misconduct and examine the precipitating factors as well as related circumstances involved. Our findings demonstrate passenger sexual misconduct takes three forms – sexual assault, sexual deviance, and sexual harassment – and highlight the complexity of circumstances, factors, and types of victims (i.e. passengers, flight attendants, and crew) involved in these reports.